(untitled) (Fiep Bulletin - online, 2019)
We know that gambling is of great importance in child development as a whole. By exploring their ability to act, think,interact, we seek psychomotricity to better understand this development at this stage of life. The child develops by interacting withother children, using objects and toys, which lack attention when handling them, and in this way the psychomotor development isclosely linked to this child development. Based on this aspect, we are looking for ways to concretize this thinking. We conducted aresearch in a kindergarten institution to better understand how children develop, using psychomotor games that need movementand attention. In order to base this analysis, we seek theoretical apparatus with Delval, Gonçalves, Oliveira, Machado andVinicius, Piaget, among others, so that we make some clarifications, in front of the data found. In this way, we will have a betterunderstanding of the stages of child development, and their particular actions during this phase.